2008
DOI: 10.1148/radiol.2492080269
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Diffuse Pulmonary Fibrosis on the Reliability of CT Signs of Pulmonary Hypertension

Abstract: PA dilatation occurs in the absence of PH in patients with pulmonary fibrosis and is therefore an unreliable sign of PH in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
5
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(114 citation statements)
references
References 31 publications
4
102
5
2
Order By: Relevance
“…Also, pulmonary artery dilatation can occur in the absence of PHT in patients with pulmonary fibrosis and is therefore an unreliable sign of PHT in this cohort [51]. Devaraj et al [52] showed that a composite index of the ratio of the diameter of the MPA and ascending aorta combined with echocardiography-derived right ventri- Right heart on multidetector CT…”
Section: Pulmonary Hypertensionmentioning
confidence: 82%
“…Also, pulmonary artery dilatation can occur in the absence of PHT in patients with pulmonary fibrosis and is therefore an unreliable sign of PHT in this cohort [51]. Devaraj et al [52] showed that a composite index of the ratio of the diameter of the MPA and ascending aorta combined with echocardiography-derived right ventri- Right heart on multidetector CT…”
Section: Pulmonary Hypertensionmentioning
confidence: 82%
“…Such a phenomenon has been described in the portal vein with advancing degrees of cirrhosis-induced portal hypertension, whereby a portal vein may not be free to fully dilate in response to elevated pressures in chronic settings because of a constricting stiff liver or vessel wall. 31 The pulmonary vasculature may be free to dilate without the constraints of an inelastic environment or restricted motion.…”
Section: Discussionmentioning
confidence: 99%
“…3 In patients with interstitial lung disease, the pulmonary artery may be dilated without the corresponding increase in pressure. 4 Dilated pulmonary arteries can cause extrinsic compression on the left main stem coronary artery (Figure 1). The left main stem is typically effaced and displaced caudally.…”
Section: Vascular Complicationsmentioning
confidence: 99%